Biocompatibility And Angiogenesis Evaluations Of Biomedical Grade Chitosan Derivative Films In Rabbits - Saifuddin, Siti Nazmin (2009)
Chitosan is composed of glucosamine and N-acetylglucosamine, which are constituents of mammalian tissues. Kitosan terdiri daripada ‘glucosamine’ dan ‘N-acetylglucosamine’ yang merupakan elemen dalam tisu mamalia.